Enhancing Business Operations through Technology: A Community-Driven Inventory System for Dymas Kulit Home-Based Leather Craft Business - Rakhmadi, Aris; Qanza, Aiza Fravy; Utomo, Ihsan Cahyo (ABDIMASTEK, 2025)
This community service project aimed to assist Toko Dymas Kulit, a home-based leather crafting business in Magetan, East Java, by developing and implementing a web-based inventory management system to replace its manual tracking process. The new system, built using PHP with the CodeIgniter framework and MySQL, was designed to improve the accuracy and efficiency of inventory management by automating tasks such as tracking stock movement and generating real-time reports. As a result, the store saw a reduction of over 50% in the time spent on inventory checks, allowing staff to focus on other essential business activities. User satisfaction was high, with a System Usability Scale (SUS) score of 73.3, reflecting the system's ease of use. This initiative not only solved operational challenges for Toko Dymas Kulit but also empowered its employees with new skills, offering a valuable model for other small businesses in the community to improve their operations through technology.